FUNGSI DAN KEWENANGAN OTORITAS JASA KEUANGAN DALAM MEMBERIKAN PERLINDUNGAN HUKUM PARA PIHAK TERHADAP EKSEKUSI HAK TANGGUNGAN - Teddy Hendrawan; Eksy Puji Rahayu (Fakultas Hukum Universitas Janabadra, 2024)
This research aims to determine the role, function, and authority of the OJK when problems arise between creditors and debtors in resolving the execution of Mortgage Rights by Commercial Banks and the legal application of the execution of Mortgage Rights by Banks in terms of Law no. 4 of 1996 concerning Mortgage Rights. This type of research uses normative legal research using statue approach and also conseptual research approach methods. Data sources consist of primary data obtained directly through interviews, secondary data obtained from official documents, books related to the research object, research results, theses, dissertation and statutory regulations. The research locations are BRI Bank Yogyakarta Branch, Sleman Yogyakarta District Court Office and OJK Office. The data analysis used is a qualitative juridical method and a deductive method to strengthen the analysis presented without using statistical formulas. The results are that the OJK has three authorities in regulating collateral execution. Legislative authority is to create regulations and supervision over the execution of guarantees which must be obeyed by finance companies (creditors) and their debtors. Authority to investigate violations in the financial services sector. And the authority of Adjudication as in resolving disputes outside of court. Based on Law no. 4 of 1996 concerning Mortgage Rights, creditors can execute Mortgage Rights by means of execution, mandatory non-execution and also voluntary non- execution auctions. Creditors tend to prefer voluntary non-execution one, however, in carrying it there are still some problems in between. In this case, the OJK applies several of its authorities to guarantee legal protection for the parties.